Cumulative pregnancy and live birth rates following intrauterine insemination and in vitro fertilization in couples with unexplained infertility: Kumulativna stopnja zanositve in živorojenih otrok pri intrauterini inseminaciji in in vitro fertilizaciji pri parih z nepojasnjeno neplodnostjo - Kozar, Nejc; Kovačič, Borut; Reljič, Milan; Kovač, Vilma (Acta Medico-Biotechnica, 2021)
Purpose: There are multiple options for the treatment of unexplained infertility. Two of the most commonly used treatments are intrauterine insemination (IUI) and in vitro fertilization (IVF). The aim of our research was to analyze and compare the success rates of IUI and IVF procedures in the treatment of unexplained infertility.Methods: This was a retrospective study including 914 cycles of IUI performed for 355 couples, and 302 IVF cycles performed for 161 couples. All cases involved unexplained infertility and were treated in our department between 2012 and 2014. We analyzed differences in pregnancy, live birth rate, multiple pregnancy rate, and predictive factors for IUI.Results:There was a significant difference between IUI and IVF in terms of cumulative pregnancy and live birth rates after 4 cycles (22.0% vs. 71.8%; p < 0.001 for clinical pregnancy rates and 16.1% vs. 64.8%for live birth rate). Differences between the two techniques in terms of twin live birth rates were not significant (16.5% for IUI vs. 17.6% for IVF; p=0.936). Using logistic regression, we found that the duration of infertility, total sperm count, and the type of stimulation, were significant predictive factors for IUI (p = 0.014, p = 0.036 and p = 0.046, respectively).Conclusion: As expected, according to pregnancy rate, IVF is a better option for the treatment of idiopathic infertility than IUI. However, IUI should not be underestimated since it offers reasonable success rates with significantly less invasiveness. To improve the outcome of treatment for unexplained infertility, we suggest that treatment methods should be chosen with respect to predictive factors.
Keywords: intrauterine insemination; in vitro fertilization; cumulative pregnancy rate; multiple pregnancy